Comparative Study of Hemostatic Parameters in Type 2 Diabetes Mellitus and Healthy Individuals - Mohammed Kareem Jabbar (Genius Journals, 2022)
Diabetes mellitus patients with persistent hyperglycemia develop coagulopathies because prothrombin, fibrinogen, and other proteins essential to the clotting process are affected. Reduced prothrombin time (PT) and activated partial thromboplastin time (APTT) show a hypercoagulable condition, which is linked to an elevated thrombotic risk and detrimental cardiovascular outcomes. The coagulation profile of type 2 diabetes mellitus was evaluated in this study. The aim of this study was to determine the blood clotting profiles and risk factors for blood clotting abnormalities in diabetic people
Keywords: Diabetes mellitus,; Hemostatic parameter comparisons